“Motherwork” and communicative labor: A gendered analysis of hunger in marginalized US women - de Souza, Rebecca (Frontiers in Communication, 2023)
The feminization of hunger plays out in communities across the globe where poverty exists, including the United States, the world’s wealthiest nation. The feminization of hunger and poverty can be traced to the “gender system”- deep seated gender inequities resulting in job segregation, discrimination in pay, unpaid caring work, and gender-based violence. This exploratory qualitative research study explores how gender informs women’s experiences of hunger and food insecurity through the lens of “motherwork” and structural vulnerability. Attending to the voices of marginalized women, the analysis identified three key themes: toxic stress related to food work, welfare stigma and racism, and the invisible loads of care work and communicative labor. The analysis shows that women’s experience of hunger and food insecurity in the US is linked to forces of economic deprivation and symbolic violence; for women and mothers their experience of food insecurity is distinct because of its gendered link to the care work, food work, and communicative labor necessary for the survival and wellbeing of children.